The strategy for enhancing consumer intention to dine at green restaurants: three-phase decision-making model. (16th April 2017) - Chen, Cheng-Ta; Lee, Wen-Hwa; Chang, Ya-Yuan; Cheng, Ching-Chan
Abstract : This study aimed to develop the strategy for enhancing consumer intention to dine at green restaurants by using a three-phase decision-making model which used structural equation modelling (SEM), decision-making trial and evaluation laboratory (DEMATEL), and quality function deployment (QFD) methods in order to determine the critical core factors affecting 'consumer intention' to dine at green restaurants, and to develop specific improvement strategies. A total of 511 customer questionnaires were returned from 10 green restaurants. This study also sequentially invited 2 groups of each 10 experts to complete the DEMATEL expert questionnaire and QFD expert questionnaire, respectively. The results of the SEM analysis showed that attitude, subjective norm, perceived difficulty, food quality, service quality, and balance of nature have significant effects on consumer intentions to dine at green restaurants. Among these six factors, four critical core factors were found by the DEMATEL analysis. According to the results of experts' focus group and QFD, this study developed six improvement schemes and assessed their improvement effects. The findings can provide a new insight based on the three-phase decision-making model to determine the most effective strategy for enhancing consumer intention to dine at green restaurants under limited resources.